Bis(vinylenedithio)tetrathiafulvalene analogues of BEDT-TTF - Ertas, Erdal; Demirtas, İlknur; Ozturk, Turan (Beilstein Journal of Organic Chemistry, 2015)
This review aims to give an overview of the current status of our research on the synthesis of π-electron donor bis(ethylenedithio)tetrathiafulvalene (BEDT-TTF, ET) analogues prepared from 1,8-diketones via a ring forming reaction. The new synthesized π-electron donors have vinyl moieties producing extended π-electron delocalization over the substituent phenyl rings at the peripheries.
Keywords: bis(ethylenedithio)tetrathiafulvalene; bis(vinylenedithio)tetrathiafulvalene; tetrathiafulvalene